Oil Palm Boom and Farm Household Diets in the Tropics - Sibhatu, Kibrom T. (Frontiers in Sustainable Food Systems, 2019)
Farm households in the tropics are rapidly expanding oil palm monocultures, mainly at the expense of rainforests, agroforests, and traditional croplands. Although monetary gains and ecological consequences of such changes in land-use have been extensively documented, little is known about nutritional and dietary impacts on farm households despite those households being the most affected by nutritional problems. Here, this research gap is addressed with a 2-year panel data of farm households from Jambi province in Indonesia, a hot spot of tropical rainforest conversion into oil palm plantation. I use endogenous switching regression to better account for selection bias and obtain counterfactual outcomes. Results show high levels of undernourishment and micronutrient inadequacy in farm households in Jambi. Non-adopters are more likely to be undernourished and micronutrients deficient, consume less diverse foods, and eat low quantities of fruits and vegetables. The counterfactual analysis shows that oil palm adoption leads to significantly greater household dietary diversity, higher calorie consumption, more fruit and vegetable consumption, and higher food expenditure in farm households. These positive dietary impacts are observed irrespective of whether households belong to transmigrant or local communities. Panel regression results further show that oil palm cultivation reduces the prevalence of undernourishment and, at the same time, increases the mean probability of adequacy of consumed fruits and vegetables and micronutrients. This impact, leading to better diets, however, is complex and not straightforward; several socioeconomic, demographic, and farm factors have different dietary impacts for adopters and non-adopters. The findings highlight important policy implications: farm households adopt and expand land-uses that provide greater dietary benefits. Thus, policy-makers interested in maintaining the tropical rainforests, regulating oil palm plantations, and tackling nutritional deficiencies in the rural tropics should not overlook these dietary benefits for farm households.